TRAINING EDUCATORS FROM THE NORTHEAST BACKLANDS IN ACTIVE METHODOLOGIES AND DIGITAL TECHNOLOGIES (CIPEEX, 2025)
The continuing professional development of teachers is a strategic component for enhancing pedagogical practices, particularly in contexts with limited access to public policies and educational programs. This study presents the partial findings of a training project on active methodologies and digital technologies, developed by the Pedagogy program at the Evangelical University of Goiás – UniEVANGÉLICA. The participants are educators affiliated with the Água Viva Institute, a non-profit social organization working in the Sertão region of Northeast Brazil. Comprising four synchronous online meetings and one in-person session, the initiative aims to foster both technical competencies—related to didactics, active methodologies, and digital technologies—and socio-emotional skills, such as empathy, leadership, and teamwork. This paper presents the dynamics and outcomes of the first synchronous meeting, which took place on September 15, 2025. The results indicate a significant acquisition of new knowledge, increased educator engagement, and a stronger sense of belonging. It is concluded that this initiative by the Pedagogy program not only broadens the pedagogical repertoires of the participants but also contributes to the re-signification of educational practices in the semi-arid region of Northeast Brazil.